IMPLICATIONS OF BLOCKCHAIN TECHNOLOGY IN CIVIL TRANSACTIONS: A REVIEW OF LEGAL ASPECTS - Letunggamu, Olfriady; Dwi Putranto, Rahmat (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study discusses the legal implications of using blockchain technology in civil transactions, focusing on aspects such as smart contracts, proof of ownership, data security, and regulation. Blockchain technology offers advantages such as transparency, security, and efficiency but also presents various legal challenges that need to be addressed. Smart contracts have the potential to be considered valid if they meet applicable contractual requirements, but their automatic and rigid execution can cause problems in certain situations. Proof of ownership recorded on the blockchain requires legal recognition to be valid and accepted in court, while the transfer of ownership through blockchain requires clear regulations to ensure its legality. In terms of data security, blockchain offers high protection but raises challenges related to privacy and compliance with data protection regulations such as GDPR. Clear and comprehensive regulations are needed to support the safe and effective adoption of blockchain, but many jurisdictions still lack an adequate legal framework. This study recommends the development of relevant regulations, increased education and awareness about blockchain, and further research to develop best practices and industry standards. With the right approach, blockchain technology can enhance efficiency, security, and trust in civil transactions.